2014
DOI: 10.1177/0891988714541872
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Testosterone Levels and Cognition in Patients With Alzheimer Disease and Nondemented Elderly Men

Abstract: Findings suggest that testosterone is not associated with most neuropsychological test performances in patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, studies suggest that the contribution of changes in androgen levels to Alzheimer’s disease may be relatively modest—particularly in women (Hogervorst and others 2005). With respect to cognitive deficits associated with Alzheimer’s disease, circulating testosterone levels do not appear to be predictive of neuropsychological outcome (Seidl and Massman 2014). Testosterone replacement therapy has also been reported to have no significant effect on motor and nonmotor symptoms of Parkinson’s disease (Okun and others 2006) although, as is the case for many clinical studies, interpretation of the results is limited by sample size.…”
Section: Evidence For Androgen Effects On Hippocampal Functionmentioning
confidence: 99%
“…However, studies suggest that the contribution of changes in androgen levels to Alzheimer’s disease may be relatively modest—particularly in women (Hogervorst and others 2005). With respect to cognitive deficits associated with Alzheimer’s disease, circulating testosterone levels do not appear to be predictive of neuropsychological outcome (Seidl and Massman 2014). Testosterone replacement therapy has also been reported to have no significant effect on motor and nonmotor symptoms of Parkinson’s disease (Okun and others 2006) although, as is the case for many clinical studies, interpretation of the results is limited by sample size.…”
Section: Evidence For Androgen Effects On Hippocampal Functionmentioning
confidence: 99%
“…there have been relatively few studies that have trialed testosterone supplementation in men with AD or mild cognitive impairments (MCI) and none have evaluated testosterone treatment in individuals that are pre-symptomatic but at a greater risk of cognitive decline. These studies have shown mixed outcomes with improvements in certain cognitive domains [6], to no improvement [7, 8]. A number of factors may account for the discrepancies in the outcomes of these trials, including differences in type, mode and dosage of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Any change or deficiency within the neural tissue is readily compensated by circulating levels in the bloodstream. Deficiency in levels of these neurosteroids has been clinically validated in AD [ 271 , 272 , 273 , 274 , 275 ], PD [ 276 , 277 ], HD [ 278 ], and MS [ 279 , 280 , 281 ]; hormonal replacement therapy depicts beneficial effects in AD [ 276 , 282 , 283 , 284 , 285 , 286 ], PD [ 276 , 277 , 287 , 288 , 289 ], HD, and MS [ 256 , 290 , 291 , 292 , 293 ].…”
Section: Future Strategiesmentioning
confidence: 99%